The School administrator and his audio-visual program - Schuller, Charles F. (Washington, D.C : Department of Audio-Visual Instruction National Education Association, 1954)
A need has long existed for a coordinated source of information for school administrators on the characteristics and requirements of an effective audio-visual program. Administrators in schools and in higher institutions of learning have been unable, as a rule, to find such information in convenient form.
Chapter One. Vitalizing the curriculum -- Chapter Two. Initiating an audio-visual -- Chapter Three. Administration of an audio-visual center -- Chapter Four. Provision of audio-visual materials, equipment, and building facilities -- Chapter Five. School production of audio-visual materials -- Chapter Six. The Selection and education of audio-visual personnel -- Chapter Seven. Curriculum improvement and the audio-visual program -- Chapter Eight. Supervision and in-service education -- Chapter Nine. The Distribution and circulation of audio-visual materials -- Chapter Ten. Financial support for the audio-visual program -- Chapter Eleven. Evaluation of the audio-visual program -- Chapter Twelve. Research related to audio-visual administration -- Chapter Thirteen. Trends and undeveloped areas.
Includes bibliographical references and index.
Keywords: AUDIO-VISUAL EDUCATION